2000
DOI: 10.1126/science.287.5460.2010
|View full text |Cite
|
Sign up to set email alerts
|

A Fossil Snake with Limbs

Abstract: A 95-million-year-old fossil snake from the Middle East documents the most extreme hindlimb development of any known member of that group, as it preserves the tibia, fibula, tarsals, metatarsals, and phalanges. It is more complete than Pachyrhachis, a second fossil snake with hindlimbs that was recently portrayed to be basal to all other snakes. Phylogenetic analysis of the relationships of the new taxon, as well as reanalysis of Pachyrhachis, shows both to be related to macrostomatans, a group that includes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
208
1
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 209 publications
(232 citation statements)
references
References 10 publications
12
208
1
11
Order By: Relevance
“…The Round Island boas Casarea dussumieri and Bolyeria multicarinata are of relatively small size compared to most other booids, yet they are nested deeply inside the latter (Underwood, 1976;Tchernov et al, 2000;Lee and Scanlon, 2002;Apesteguia and Zaher, 2006;Scanlon, 2006). Thus, some degree of paedomorphosis may be expected, as was indeed noted by Anthony and Guibé (1952).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The Round Island boas Casarea dussumieri and Bolyeria multicarinata are of relatively small size compared to most other booids, yet they are nested deeply inside the latter (Underwood, 1976;Tchernov et al, 2000;Lee and Scanlon, 2002;Apesteguia and Zaher, 2006;Scanlon, 2006). Thus, some degree of paedomorphosis may be expected, as was indeed noted by Anthony and Guibé (1952).…”
Section: Discussionmentioning
confidence: 84%
“…2;Tchernov et al, 2000;Apesteguia and Zaher, 2006). These phylogenetic hypotheses stand in stark contrast to the recent findings based on molecular data, which place bolyeriids as sister-taxon to a clade that includes the uropeltines (traditionally considered non-macrostomatan), Acrochordus and colubroids, whereas the tropidophiids were found to be the sister-taxon of the non-macrostomatan genus Anilius (Vidal and Hedges, 2004; see also Vidal and David, 2004).…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Our results corroborate Lawson et al (2005) in positioning Acrochordus as the sister group to all other caenophidians. A sister-group relationship between Acrochordus and other caenophidians is a wellsupported hypothesis in all recent morphological phylogenetic analyses (Tchernov et al, 2000;Lee & Scanlon, 2002;Apesteguía & Zaher, 2006), as well as other molecular studies and combined molecular/ morphological analyses (Gravlund, 2001;Lee et al, 2004; and references therein). In contrast, Kelly et al (2003) and Kraus & Brown (1998) found Acrochor-dus to cluster with Xenodermus-Achalinus (Xenodermatinae); in addition, Kraus & Brown (1998) found their Acrochordus-xenodermatine clade to cluster well within other caenophidians.…”
Section: Discussionmentioning
confidence: 92%